2007
DOI: 10.1017/s1751731107705311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary sulphur sources on concentrations of hydrogen sulphide in the rumen head-space gas of dairy cows

Abstract: Three change-over design experiments investigated the origin of hydrogen sulphide in the rumen head-space gas of dairy cows, comparing the effects of single iso-S additions of methionine, cysteine and sodium sulphate, as well as the effects of single meals of fresh ryegrass or white clover. The concentration of hydrogen sulphide in rumen gas declined close to zero within 4 h after withdrawal of the previous feed. Sulphur sources were then given to cows and concentrations of hydrogen sulphide recorded in rumen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Methionine in SBM was much less degradable than in the other protein sources (MGF and SFM). The degradability of methionine was always lower than cystine, confirming the results of Dewhurst et al (2007). The batches of MGF differing in colour also differed in S degradability, as well in concentrations of hydrogen sulphide in rumen headspace gas.…”
Section: Protein Sourcessupporting
confidence: 79%
See 3 more Smart Citations
“…Methionine in SBM was much less degradable than in the other protein sources (MGF and SFM). The degradability of methionine was always lower than cystine, confirming the results of Dewhurst et al (2007). The batches of MGF differing in colour also differed in S degradability, as well in concentrations of hydrogen sulphide in rumen headspace gas.…”
Section: Protein Sourcessupporting
confidence: 79%
“…Concentration of hydrogen sulphide in the rumen headspace gas Dewhurst et al (2007) confirmed that cyst(e)ine is the dominant source of hydrogen sulphide in rumen gas and showed that there was a linear increase in hydrogen sulphide concentrations in response to increasing cysteine additions. In Expt 1, the concentration of hydrogen sulphide was very different between protein sources, with MGF having the highest concentration followed by SFM and SBM leading to a very low concentration.…”
Section: Protein Sourcesmentioning
confidence: 60%
See 2 more Smart Citations
“…1987, Gooneratne et al 1989, Sager et al 1990, Gould et al 1991, Hamlen et al 1993, Jeffrey et al 1994, McAllister et al 1997, Loneragan et al 1998, Gould 1998, Gould 2000, Niles et al 2000, Loneragan et al 2001, Niles et al 2002, Haydock 2003, Loneragan et al 2005, Kul et al 2006, Dewhurst et al 2007, McKenzie et al 2009). Outras etiologias descritas foram deficiência da tiamina (Jensen et al 1956, Edwin & Jackman 1973, intoxicação por cloreto de sódio associada à privação de água (Trueman & Clague 1978, Osweiler et al 1995, intoxicação por chumbo (Christian & Tryphonas 1971), ingestão de melaço (Mella et al 1976) ou de plantas ricas em tiaminases (Pritchard & Eggleston 1978) e infecção por herpesvírus bovino 5 (BoHV-5) (Perez et al 2003, Rissi et al 2008.…”
Section: Introductionunclassified